PENGELOLAAN KECEMASAN DAN KETIDAKPASTIAN DALAM PROSES KOMUNIKASI ANTARBUDAYA MAHASISWA MUSI RAWAS UTARA DI UNIVERSITAS KEBANGSAAN REPUBLIK INDONESIA - Nurjannah; Suhaeri (UKRI, 2025)
Students who live away from home often face challenges in intercultural communication, when they have to adapt to the norms, values, and customs of their home culture. This is the case for students from Musi Rawas Utara at Universitas Kebangsaan Republik Indonesia (UKRI), who experience anxiety and uncertainty in the process of intercultural communication. This study aims to analyze the strategies used by Musi Rawas Utara students to manage anxiety and uncertainty based on the Anxiety/Uncertainty Management (AUM) Theory. The research employed a qualitative method with a descriptive approach and an interpretive paradigm. Data were collected through interviews and observations, then analyzed through reduction, presentation, triangulation, and conclusion drawing. The findings show that Musi Rawas Utara students manage anxiety and uncertainty through seven categories: self-concept, motivation to interact, responses to strangers, social categorization, situational processes, social connections, and ethical interaction. These efforts have proven effective in reducing anxiety levels and enhancing the effectiveness of intercultural communication. The study concludes that the management of anxiety and uncertainty is both a psychological matter and a social process that carries ethical values, thus supporting the achievement of bicultural adaptation among migrant students.